THE EFFECT OF TERMITES EXTRACT ON INHIBITION OF GROWTH OF SOME PATHOGENIC BACTERIA AND SYNTHESIS OF BIOFILM - G.M. Saleh; S.A.Alash; H.Y. Fadhil; H.B.Ali. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study was aimed to extract the effective material from the dry nests of termites and detect its antibacterial activity against some pathogenic bacterial isolates and inhibit synthesis of its biofilm. Termites dry nests were collected and the effective material was extracted then the antibacterial activity was detected using the disc diffusion assay. Results were showed that the extract have antibacterial material from the Termites dry nests, this extract showed antibacterial activity against Gram positive bacteria (Staphylococcus aureus) at (21.5mm) and Gram negative bacteria ( Enterobacter sp. and Pseudomonas aeruginosa) at (26 mm and 20 mm) respectively by inhibiting their growth, as well as its effect on biofilm production of pathogenic bacteria. Staphylococcus aureus, Enterobacter sp. and Pseudomonas aeruginosa revealed a significant decrease (P<0.01) in biofilm synthesis as the concentration of the extract increased.